The rate of muscle temperature increase during acute whole-body vibration exercise - Cochrane, D. J.; Stannard, S. R.; Sargeant, A. J.; Rittweger, J. (European Journal of Applied Physiology, 2008)
This study compared the rate of muscle temperature (T m) increase during acute whole-body vibration (WBV), to that of stationary cycling and passive warm-up. Additionally we wanted to determine if the purported increase in counter-movement jump and peak power cycling from acute WBV could be explained by changes in muscle temperature. Eight active participants volunteered for the study, which involved a rest period of 30 min to collect baseline measures of muscle, core, skin temperature, heart rate (HR), and thermal leg sensation (TLS), which was followed by three vertical jumps and 5 s maximal cycle performance test. A second rest period of 40 min was enforced followed by the intervention and performance tests. The change in T m elicited during cycling was matched in the hot bath and WBV interventions. Therefore cycling was performed first, proceeded by, in a random order of hot bath and acute WBV. The rate of T m was significantly greater (P < 0.001) during acute WBV (0.30°C min-1) compared to cycle (0.15°C min-1) and hot bath (0.09°C min-1) however there was no difference between the cycle and hot bath, and the metabolic rate was the same in cycling and WBV (19 mL kg-1 min-1). All three interventions showed a significant (P < 0.001) increase in countermovement jump peak power and height. For the 5 s maximal cycle test (MIC) there were no significant differences in peak power between the three interventions. In conclusion, acute WBV elevates T m more quickly than traditional forms of cycling and passive warm-up. Given that all three warm-up methods yielded the same increase in peak power output, we propose that the main effect is caused by the increase in T m.